DESAIN LEMBAR KERJA PESERTA DIDIK (LKPD) TERINTEGRASI PROBLEM BASED LEARNING (PBL) UNTUK MEMFASILITASI KEMAMPUAN BERPIKIR KREATIF SISWA - Ardha, Muhammad Ayasi; Emiliannur, Emiliannur (Jurnal MIPA dan Pembelajarannya, 2025)
Education in the 21st century demands various skills that a person must master, facing these challenges, one of the skills that can be trained students is the ability and skills of creative thinking (Creativity), following the 21st-century skills needed by students, namely the 4C skills. This study aims to design a Student Worksheet (LKPD) integrated with the Problem-Based Learning (PBL) model to facilitate students' creative thinking skills in physics learning, especially in alternative energy materials. The research method used is development research with the ADDIE model. The subjects of this research product trial are students from class X and physics teachers of SMAN 1 Padang Ganting. Meanwhile, the object of the research is the integrated LKPD PBL to facilitate creative thinking skills. The validity criteria for LKPD were obtained as a result of 91% (very valid). The practicality criteria of LKPD by teachers were obtained 96.8% (very practical) and the level of practicality by students was 89.2% (very practical). Thus, this PBL-integrated LKPD is expected to be an effective and interesting learning resource and help students understand physics concepts.